Enhanced star formation in z ∼ 6 quasar companions. Issue 2 (11th April 2022) - Zana, Tommaso; Gallerani, Simona; Carniani, Stefano; Vito, Fabio; Ferrara, Andrea; Lupi, Alessandro; Di Mascia, Fabio; Barai, Paramita
ABSTRACT: Quasars powered by supermassive black holes (>10 8 M⊙ ) at z ∼ 6 are predicted to reside in cosmic overdense regions. However, observations so far could not confirm this expectation due to limited statistics. The picture is further complicated by the possible effects of quasar outflows (i.e. feedback) that could either suppress or stimulate the star formation rate (SFR) of companion galaxies, thus modifying the expected bias. Here, we quantify feedback effects on the properties and detectability of companions by comparing cosmological zoom-in simulations of a quasar in which feedback is either included or turned-off. With respect to the no-feedback case, companions (a) directly impacted by the outflow have their SFR increased by a factor of 2−3, and (b) tend to be more massive. Both effects shift the [C ii ] 158 μ m and UV luminosity functions towards brighter magnitudes. This leads us to conclude that quasar feedback slightly increases the effective quasar bias, boosting the number density of observable quasar companions, in agreement with what has been found around the brightest quasars of recent Atacama Large Millimeter Array (ALMA) [C ii ] surveys. Deeper observations performed with James Webb Space Telescope and/or ALMA will improve the statistical significance of this result by detecting a larger number of fainter quasar companions.